An edge computing architecture in the Internet of Things - Martín-Fernández, Cristian; Díaz-Rodríguez, Manuel; Rubio-Muñoz, Bartolomé (IEEE, 2018)
In the last few years, the Internet of Things (IoT) has emerged as the new disruptive technology to change the world. Cloud computing has accompanied this field to overcome its processing and storage limitations. However, this evolution has originated a huge increase in IoT devices and data that will create a bottleneck for current networks, in addition to a lack of low latency in cloud communications. Edge computing has been developed to address this challenge, moving the processing to the edge of the network. In this paper, an edge computing architecture is presented to overcome these challenges. The architecture, based on our previous work on the λ-CoAP architecture, covers the whole vision of an edge computing deployment, from IoT devices, to the edge Smart Gateways and up to a cloud infrastructure.
https://conferences.ieeeauthorcenter.ieee.org/author-ethics/guidelines-and-policies/post-publication-policies/
Keywords: Internet de los objetos; Informática en la nube; Computer architecture; Cloud computing; Edge computing; Virtualization